Effectiveness of Enterovirus 71 inactivated vaccines against hand, foot, and mouth disease: A test-negative case-control study - Yutong Zhang; Jinzhao Cui; Fengfeng Liu; Yang Song; Quanyi Wang; Yanzhe Liu; Yanping Zhang; Zhongjie Li; Zhaorui Chang (Taylor & Francis Group, 2024)
ABSTRACTThe Enterovirus A71 (EV-A71) vaccine was introduced in China in December 2015 as a preventive measure against hand, foot, and mouth disease (HFMD) caused by EV-A71. However, the effectiveness of the vaccine (VE) in real-world settings needs to be evaluated. We conducted a test-negative case-control study to assess the effectiveness of EV-A71 vaccines in preventing EV-A71-associated HFMD. Children aged 6-71 months with HFMD were enrolled as participants. The case group comprised those who tested positive for EV-A71, while the control group comprised those who tested negative for EV-A71. To estimate VE, a logistic regression model was employed, adjusting for potential confounders including age, gender, and clinical severity. In total, 3223 children aged 6 to 71 months were included in the study, with 162 in the case group and 3061 in the control group. The proportion of children who received EV-A71 vaccination was significantly lower in the case group compared to the control group (p < .001). The overall VEadj was estimated to be 90.8%. The VEadj estimates for partially and fully vaccinated children were 90.1% and 90.9%, respectively. Stratified by age group, the VEadj estimates were 88.7% for 6 to 35-month-olds and 95.5% for 36 to 71-month-olds. Regarding disease severity, the VEadj estimates were 86.3% for mild cases and 100% for severe cases. Sensitivity analysis showed minimal changes in the VE point estimates, with most changing by no more than 1% point. Our study demonstrates a high level of vaccine effectiveness against EV-A71-HFMD, especially in severe cases. Active promotion of EV-A71 vaccination is an effective strategy in preventing EV-A71 infections.